(untitled) (The Journal of Plant Protection Sciences, 2021)
The litchi (Litchi chinensis Sonn.) is one of the 0.008%, azadirachtin 0.15% EC at 5ml/L, important fruits growing in the tropical and sub- Azadirachtin 1% EC at 3 ml/L ,4ml/L 6ml/L and tropical regions. It has high export potential. there was one untreated control. Each treatment Litchi is infested by eleven major and minor was replicated 5 times.